Exploring EFL Students' Attitudes Toward Online Learning: A Qualitative Study of Sixth-Semester Students at the Faculty of Language and Arts - Jelita Purnamasari Gulo; Elisabet A Butarbutar; Murni Murni; Nayla Firzanah (Faculty of Tarbiyah nad Teacher Training, 2026)
This study explores EFL sixth-semester students’ attitudes toward online learning in English classes at the Faculty of Language and Arts, State University of Medan, and identifies the factors influencing those attitudes. Online learning has become an important part of higher education, yet EFL students often experience both benefits and challenges in digital learning environments, particularly in relation to interaction, motivation, and language practice. This research employed a descriptive qualitative design involving three participants for semi-structured interviews and 20 participants for an online questionnaire. The data were analyzed using Miles, Huberman, and Saldaña’s interactive model through data condensation, data display, and conclusion drawing. The findings show that students’ attitudes toward online learning were shaped by cognitive, affective, and behavioral dimensions. Cognitively, most students doubted the effectiveness of online English classes in improving proficiency, although they acknowledged some benefits in speaking practice and vocabulary exposure. Affectively, students generally showed positive feelings such as enthusiasm and comfort, but these emotions were strongly influenced by class atmosphere and interaction. Behaviorally, most students were active in attending classes and seeking additional learning resources, although participation sometimes depended on confidence and workload. The influencing factors were divided into internal factors, such as motivation, self-confidence, and previous learning experience, and external factors, such as internet connectivity, teaching methods, and the online learning platform. Overall, the study reveals that students’ attitudes toward online learning are complex and shaped by both personal and contextual conditions.